The Effect of Leader Member Exchange, Employee Participation in Decision Making, Affective Commitments on Organization Citizenship Behavior on Employees of Automotive Auction Service Companies in West Jakarta - Gunawan P, Andreas Wahyu; Rahayu, Sarfliyanti Anggaini; Aseanty, Deasy (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the influence of Leader Member Exchange, Employee Participation in Commitments, Affective Commitments on Organization Citizenship Behavior. The design of this research was carried out through the use of hypothesis testing. This data collection took place cross-sectionally. The data used in the research is primary data and was collected by distributing questionnaires via g-from which were filled in by employees of automotive auction companies. The sample collection method was purposive sampling method of 125 employees. The data processing technique used in this research is testing instruments such as validity and reliability as well as structural equation modeling (SEM) using SPSS and AMOS. The research results show that Leader Member Exchange has a positive effect on Organization Citizenship Behavior, Employee Participation in Commitments has a positive effect on Organization Citizenship Behavior, Affective Commitments has a positive effect on Organization Citizenship Behavior. The managerial implication that can be given to companies is that companies can further improve Organizational Citizenship Behavior among employees through the implementation of Leader Member Exchange, Employee Participation In Commitments, Affective Commitments in carrying out their work.